Characterization of serratia spp. from aquaculture enviroment and river of Kubah National Park - Victoria, Druce (Universiti Malaysia Sarawak (UNIMAS), 2012)
Serratia spp. is an opportunistic gram negative bacterium under the family of Enterobacteriaceae. Some species such as Serratia marcescens is related with the significant outbreak of nosocomial infections of severities in patients. In this study, Serratia spp. was isolated from aquaculture environment and the river. Biochemical tests comprised of IMViC and string test were conducted for the identification of bacteria isolates from the river water of Kubah National Park. The further identification of the isolates were carried out using API 20E kit. Genetic characterization of the isolates was carried out by ERIC-PCR to analyse their genetic diversity. Phylogenetic tree was constructed based on DNA fingerprinting using RAPD software to illustrate the relationship among the bacteria isolates from these two environments. Based on the phylogenetic tree dendrogram, aU the isolates can be categorised into 3 major clusters of similarity. The phylogenetic tree created for DNA fingerprinting technique indicated that the population of the isolates in both environments are greatly diverse.